Sociolinguistic variation in Old English records of communities and people - Timofeeva, Olga (Advances in historical sociolinguistics ;, 2022)
"This is the first extensive study of Old English to utilise the insights and methodologies of sociolinguistics. Building on previous philological and historical work, it takes into account the sociology and social dialectology of Old English and offers a description of its speech communities informed by the theory of social networks and communities of practice. Specifically, this book uses data from historical narratives and legal documents and examines the interplay of linguistic innovation, variation, and change with such sociolinguistic parameters as region, scribal office, gender, and social status. Special attention is given to the processes of supralocalisation and their correlation with periods of political centralisation in the history of Anglo-Saxon England"--